2020
DOI: 10.26434/chemrxiv.12100599.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Caffeinated Interfaces Enhance Alkaline Hydrogen Electrocatalysis

Abstract: <p>The high Pt loading required for hydrogen oxidation (HOR) and evolution (HER) reactions in alkaline fuel cells and electrolyzers adversely impacts the system cost. Here, we demonstrate the use of caffeine as a ‘double-layer dopant’ to enhance both the HER and HOR of Pt electrodes in base. HER/HOR rates increase by fivefold on Pt(111) and are accelerated on Pt(110), Pt(pc), and Pt/C as well. FTIR spectroscopy confirms that caffeine is adsorbed at the Pt surface, forming a self-limiting film through ele… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…We first verified that adding 10 -5 M caffeine into 0.1 M KOH electrolyte markedly improved the HER/HOR activity of Pt/C (TKK, 47.7 wt%) (Fig. S1A) in a RDE as originally reported by Snyder and co-workers (18). We then tested 10 -5 M 1,3-dimethyluracil and 1methylimidazole, the left and right parts of caffeine, respectively, to specify which part(s) of caffeine contribute to the improvement.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…We first verified that adding 10 -5 M caffeine into 0.1 M KOH electrolyte markedly improved the HER/HOR activity of Pt/C (TKK, 47.7 wt%) (Fig. S1A) in a RDE as originally reported by Snyder and co-workers (18). We then tested 10 -5 M 1,3-dimethyluracil and 1methylimidazole, the left and right parts of caffeine, respectively, to specify which part(s) of caffeine contribute to the improvement.…”
supporting
confidence: 81%
“…S9). The same phenomenon was also observed for caffeine (18). This phenomenon indicates that N-methylimidazoles inhibit rather than facilitate hydroxide adsorption like Ru (6).…”
supporting
confidence: 71%
See 1 more Smart Citation
“…1−4 Electrocatalysis is one of the most powerful methods to promote the reaction efficiency. 5,6 It has been shown that most noble metals exhibit good catalytic water-splitting performance due to their low potential and high chemical activity. However, their high cost and scarcity hinder further large-scale application.…”
Section: Introductionmentioning
confidence: 99%
“…9−11 It has also been demonstrated that CO 2 reduction selectivity may be tuned when catalytically active surfaces are confined by flat organic molecules. 12−14 Specifically, for hydrogen evolution, HER rates are enhanced when Pt(111) is covered by flat caffeine molecules, 15 and electrode stability is improved when Pt is confined by SiO x nanomembranes. 16−18 The effect of overlayer confinement on single crystals has also been studied with density functional theory (DFT) calculations.…”
Section: Introductionmentioning
confidence: 99%